Little Ice Age glaciers in Britain: Glacier–climate modelling in the Cairngorm Mountains. (February 2014) - Harrison, Stephan; Rowan, Ann V; Glasser, Neil F; Knight, Jasper; Plummer, Mitchell A; Mills, Stephanie C
It is widely believed that the last glaciers in the British Isles disappeared at the end of the Younger Dryas stadial (12.9–11.7 cal. kyr BP). Here, we use a glacier–climate model driven by data from local weather stations to show for the first time that glaciers developed during the Little Ice Age (LIA) in the Cairngorm Mountains. Our model is forced from contemporary conditions by a realistic difference in mean annual air temperature of −1.5°C and an increase in annual precipitation of 10%, and confirmed by sensitivity analyses. These results are supported by the presence of small boulder moraines well within Younger Dryas ice limits, and by a dating programme on a moraine in one cirque. As a result, we argue that the last glaciers in the Cairngorm Mountains (and perhaps elsewhere in upland Britain) existed in the LIA within the last few hundred years, rather than during the Younger Dryas.